The Importance of Police Management in Romania - Ioan Sidău (Ovidius University Annals: Economic Sciences Series, 2022)
The history of the Romanian principalities finally leads to the Union (one by one) of three principalities. However, the first two principalities that United at the end of the 19 century, namely Moldavia and Wallachia, had a troubled history, strongly influenced by the Ottoman Empire. Public order was almost non-existent, most of the national archives presenting a bleak landscape of Romanian public life. However, the first efforts to organize an institution that aims public order in Romania should be appreciated. Until the law of 1903 that guaranteed its existence, the Romanian Police had certain institutional precursors, which must be identified, and the purpose of this article is to do exactly that.